MODEL KEBUTUHAN PENUMPANG BANDAR UDARA SULTAN SYARIF KASIM II PEKANBARU - Pada Lumba; Rismalinda - (Jurnal APTEK, 2012)
SSK II airport in 2007 has a capacity of 1.8 million passengers per year with an area of terminal building are 6700 m2. Airport with an area of 6700 m2 should have a capacity of approximately 800 thousand to 1 million passengers per year. This means that the condition of SSK II Airport Pekanbaru is not suitable for use as this will impact on the quality of passenger service at the Sultan Sharif Kasim II airport.For that condition, analysis needs to be done to get the models arrival and departure passengers at the existing condition. The independent variables used in this study are: amount of population (X1), PDRB (X2), number of moderate and large industrial companies (X3), number of students (X4), number of lecturer (X5), export (X6), imports (X7), number of hotel rooms (X8), number of foreign tourists (X9).